Endovascular treatment of intracranial aneurysms: review of current practice. Issue 1023 (11th October 2010) - Currie, Stuart; Mankad, Kshitij; Goddard, Anthony
Abstract : Subarachnoid haemorrhage remains a major cause of morbidity and mortality throughout the world. Of those suffering the condition, 15% are known to die before they reach hospital and half of all patients die within 1 month of presentation. Of those patients who survive the initial 30 days, just under half are believed to remain dependent for their normal activities of daily living. In the vast majority of cases, SAH results from the rupture of an intracranial aneurysm. After patient stabilisation, primary treatment is focused on the prevention of re-bleeding. Until recently, this exclusively involved the surgical clipping of the ruptured aneurysm via a craniotomy. The early 1990s, with the introduction of aneurysmal coiling via endovascular intervention, heralded the dawn of a new treatment option. Presently, endovascular therapy largely supersedes surgical intervention in the management of intracranial aneurysms in the developed world. Moreover, with the emergence of new technologies and approaches for the treatment of aneurysms, the field of neurovascular intervention is only likely to expand further. However, due to its relative infancy, unanswered questions regarding long term endovascular outcome remain. This is particularly pertinent to newer techniques of embolisation for which data on complete aneurysmal occlusion rates are limited. Thus, to understand fully the capability and limitations of this treatment, further well constructed randomised controlled trials are a necessity.